"GPS in my Salad?" A Mixed Method Study of Consumers' Perception of Biomarkers in Organic Vegetables. Issue 1 (1st January 2023) - Martini, Mara; Loera, Barbara; Murphy, Blain; Dean, Moira; Dansero, Egidio; Fedi, Angela
Abstract: The paper explored consumer acceptability of a biomarker solution for organic vegetables aimed at enhancing consumer trust, using a sequential mixed-method design. Five focus groups were conducted (N = 34) to explore consumer reactions to this technology and possible nomenclatures (Study 1). Subsequently, a survey in four European countries (Germany, Italy, Poland, UK; N = 1035) analyzed consumer attitudes and acceptability of biomarker technology, considering intercountry similarities and differences (Study 2). Qualitative analyses highlighted multiple contrasting reactions to biomarkers for organic vegetables in terms of acceptability, confirmed by quantitative data analyses. Results indicated a complex relationship between the perception of biomarkers and consumer trust.